Input Training Matters in L2 Syntactic Representation Entrenchment: Evidence from a Follow-Up ERP Study - Deng, Taiping; Chen, Baoguo (Journal of psycholinguistic research, 2019)
The usage-based theory highlights the important role of linguistic input in language acquisition, and assumes that syntactic representations could be entrenched through usage or exposure. In the present study, we used the event-related potential technique to investigate the long-term effect of input training on second language (L2) syntactic representations entrenchment, using English subject-verb agreement structures as the stimuli. Results showed that 3 months after the training of the specific subject-verb agreement structures, a significant P600 was observed in the key region (the verb) of the sentences with syntactic violations in the experimental group, but not in the control group. This indicates that linguistic input training contributes to syntactic representations entrenchment, which can be sustained for a relatively long period, indicating a long-term effect of input training. The results suggest that linguistic input is a causal variable in L2 online syntactic processing, supporting the usage-based theory.